Apology of a Madman - Amon, Théo (RUS (Sao Paulo), 2020)
A full translation of Apologie d'un fou (1836/7), the text Pyotr Chaadayev (1794–1856) wrote after being officially declared insane in the aftermath of his First Philosophical Letter (1829). In this earlier, idealist and religion-oriented essay, Chaadayev had argued that Russia still had not a civilizational history of its own and fed on precarious imports which were not the result of an organic moral and intellectual progress. This fatalistic outlook meant that Russia, stuck between Europe and Asia, had not learned anything over time. It was a backward cultural nullity doomed to historical solitude. Without a past integrated with Catholic Christendom and European philosophic-political development, Russia played no role in the modern Western culture. Initially a fairly well-known manuscript written in French, this text was eventually published (1836), in Russian translation, in the journal The Telescope. The ensuing scandal was such that the journal was closed, its published was exiled, and the censure official involved was dismissed. Chaadayev was interdicted as a madman, prohibited from publishing, and for a month had to endure visits by a police officer and a psychiatrist who confirmed he was still insane and should be kept in house arrest. Apology of a Madman, written in French as well, apparently would eventually become a small treatise of philosophy of history applied to the Russian case where the author would amend some extreme positions he had championed in the Philosophical Letter but alto reaffirm its basic rationale and develop it in new directions. The work however never went beyond the fragment translated here, and was published only posthumously in 1862. It is one of the basic documents of the later controversy between Westernizers and Slavophiles, who would alternately claim for their respective doctrines the initial impulse given by Chaadayev.